1961
DOI: 10.1016/s0006-3495(61)86885-9
|View full text |Cite
|
Sign up to set email alerts
|

Studies of E. coli Ribosomal RNA and Its Degradation Products

Abstract: The RNA of E. coli ribosomes has been extracted by the phenol method. The 70S ribosomes contain RNA molecules of 28 and 18S almost exclusively. When the 70S ribosomes are dissociated to 30 and 50S ribosomes the former contain only the 18S RNA and the latter a mixture of 28 and 18S RNA. There are also present, however, small quantities of ribosomal RNA having sedimentation coefficients of between 4 and 8S. These small molecules are particularly abundant in the smaller ribosomes present in the cell extract and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1961
1961
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Sedimentation Properties, The schlieren pattern of the unfractionated ribosomal RNA is depicted in Figure 1. This distribution is characteristic of E. coli ribosomal RNA and has been widely quoted in the literature (Littauer and Eisenberg, 1959;Hall and Doty, 1959; Aronson and McCarthy, 1961). The dependence of the sedimentation coefficients upon the total RNA concentration is illustrated in Figure 2 and the effect of ionic strength in Figure 3.…”
Section: Resultssupporting
confidence: 61%
“…Sedimentation Properties, The schlieren pattern of the unfractionated ribosomal RNA is depicted in Figure 1. This distribution is characteristic of E. coli ribosomal RNA and has been widely quoted in the literature (Littauer and Eisenberg, 1959;Hall and Doty, 1959; Aronson and McCarthy, 1961). The dependence of the sedimentation coefficients upon the total RNA concentration is illustrated in Figure 2 and the effect of ionic strength in Figure 3.…”
Section: Resultssupporting
confidence: 61%
“…Several distinct RNA species have been detected during the last years in addition to the “classical” three RNA classes, mRNA [ 5 , 6 ], rRNA [ 7 ] and tRNA [ 8 ] that helped describe the central dogma of Molecular Biology established as such later [ 9 ]. The vast majority of those RNA species is known to not encode polypeptides; they are, therefore, collectively branded as non-coding RNAs or ncRNA [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Aronson & McCarthy (1961) have suggested that 16s and 23s ribosomal RNAs are built from multiples of a single subunit, the 23s particle being viewed as a dimer of 16s RNA. This view is supported by the work of Spahr & Tissieres (1959), which showed that the 30s and 50s ribosomes of Escherichia coli had similar nucleotide compositions, and the work of Petermann & Pavlovec (1963), which indicated that there was interconversion between the 18s and 28s RNA particles of rat liver ribosomes.…”
Section: Introductionmentioning
confidence: 99%